PENERAPAN MODEL PEMBELAJARAN MIND MAPPING UNTUK MENINGKATKAN KEAKTIFAN BELAJAR DAN KEMAMPUAN BERPIKIR KREATIF - Wendy Liza Mustika; Herman Lusa; Panut Setiono (JURIDIKDAS, 2023)
This study aims to describe the application of the Mind Mapping learning model and to analyze the increase in learning activeness and creative thinking abilities of students in Thematic learning for class V Elementary School 171 Rejang Lebong. This research is a Classroom Action Research (PTK) with students of class V Elementary School 171 Rejang Lebong in the academic year 2020/2021 as the subjects; consists of 21 students, 9 male students and 12 female students. This study consisted of 2 cycles, each cycle consisted of 3 meetings. The data collection was observation techniques, then followed by analyzing the data using a formula that is processed descriptively, namely quantitative analysis. The research instrument was an observation sheet of learning activeness and creative thinking ability. The results showed that the implementation of the Mind Mapping learning model had increased from Cycle I to Cycle II. It can be seen from the increased activeness and creative thinking ability of the students. The average result of the learning activeness of the students in the first cycle was 58.15% in the sufficient category, then increased to 79.19% in the second cycle in the good category. The average result of students’ creative thingking abilitu in the first cycle was 59.79% in the sufficient category, then increased to 77.14% in the good category. Therefore, the application of the Mind Mapping learning model can increase learning activeness and creative thinking ability for fifth grade students of Elementary School 171 Rejang Lebong.